Human Resource Management (HRM) practices adopted in the government building construction projects in Sindh - Abro, Ahmed Khan; Memon, Nafees Ahmed; Ali, Sajjad; Mubin, Muhammad (Tropical Scientific Journal, 2023)
ABSTRACT Objective: This paper aims to identify HRM practices along with their attributes adopted in the construction organizations in Sindh. Research Method: In depth study was carried out on HRM practices from literature review. From literature review, various HRM practices were identified through mapping. However, for identification of the HRM practices along with their attributes in the government building construction organizations, two questionnaires were designed for collection of the data. Then the collected data was analyzed on excel sheet and SPSS ver.25 for obtaining the results. Findings: Results were arrived at finding 13 HRM practices from the literature review and first questionnaire survey. Furthermore, from 13 HRM practices, top four HRM practices were taken for further analysis obtained in the form of attributes with low; medium and high perception category. No any HRM practices fell into low category; however, attributes to HRM practices were mostly in medium category and to some extent in high category. The results obtained displayed the need for improving the HRM practices in the construction sectors in Sindh. Originality: The study’s objective is to identify the attributes of HRM practices in construction industry in Sindh. The results obtained are distinctive with respect to construction industry in Sindh. Moreover, it would help construction industry in Sindh to improve HRM practices based on the identified attributes in this study.